Impact of the anodization time on the photocatalytic activity of TiO2 nanotubes - Díaz-Real, Jesús A.; Dubed-Bandomo, Geyla C.; Galindo-de-la-Rosa, Juan; Arriaga, Luis G.; Ledesma-García, Janet; Alonso-Vante, Nicolas (Beilstein Journal of Nanotechnology, 2018)
Titanium oxide nanotubes (TNTs) were anodically grown in ethylene glycol electrolyte. The influence of the anodization time on their physicochemical and photoelectrochemical properties was evaluated. Concomitant with the anodization time, the NT length, fluorine content, and capacitance of the space charge region increased, affecting the opto-electronic properties (bandgap, bathochromic shift, band-edge position) and surface hydrophilicity of TiO2 NTs. These properties are at the origin of the photocatalytic activity (PCA), as proved with the photooxidation of methylene blue.
Keywords: fluorine doping; nanotubes; photocatalytic activity; photoelectrochemistry; titanium(IV) oxide (TiO2)

(untitled) - Fujishima, A.; Honda, K. (Nature, 1972)

(untitled) - Mora-Seró, I.; Villarreal, T. L.; Bisquert, J.; Pitarch, Á.; Gómez, R.; Salvador, P. (J. Phys. Chem. B, 2005)

(untitled) - Wahl, A.; Ulmann, M.; Carroy, A.; Jermann, B.; Dolata, M.; Kedzierzawski, P.; Chatelain, C.; Monnier, A.; Augustynski, J. (J. Electroanal. Chem., 1995)

(untitled) - Yamashita, H.; Harada, M.; Misaka, J.; Takeuchi, M.; Neppolian, B.; Anpo, M. (Catal. Today, 2003)

(untitled) - Yang, L.; Li, X.; Wang, Z.; Shen, Y.; Liu, M. (Appl. Surf. Sci., 2017)

(untitled) - Haider, A. J.; Al-Anbari, R. H.; Kadhim, G. R.; Salame, C. T. (Energy Procedia, 2017)

(untitled) - Sangchay, W.; Sikong, L.; Kooptarnond, K. (Procedia Eng., 2012)

(untitled) - Filippo, E.; Carlucci, C.; Capodilupo, A. L.; Perulli, P.; Conciauro, F.; Corrente, G. A.; Gigli, G.; Ciccarella, G. (Appl. Surf. Sci., 2015)

(untitled) - Hwang, Y. J.; Yang, S.; Lee, H. (Appl. Catal., B, 2017)

(untitled) - Chen, Y.; Li, X.; Bi, Z.; He, X.; Xu, X.; Gao, X. (Electrochim. Acta, 2017)

(untitled) - Mor, G. K.; Varghese, O. K.; Paulose, M.; Mukherjee, N.; Grimes, C. A. (J. Mater. Res., 2003)

(untitled) - Mor, G. K.; Varghese, O. K.; Paulose, M.; Shankar, K.; Grimes, C. A. (Sol. Energy Mater. Sol. Cells, 2006)

(untitled) - Macak, J. M.; Hildebrand, H.; Marten-Jahns, U.; Schmuki, P. (J. Electroanal. Chem., 2008)

(untitled) - Liu, S.; Qu, X. (Appl. Surf. Sci., 2017)

(untitled) - Gao, Q.; Duan, L.; Zhang, X.; Kamiya, I.; Lü, W. (Superlattices Microstruct., 2017)

(untitled) - Yu, J. C.-C.; Nguyen, V.-H.; Lasek, J.; Wu, J. C. S. (Appl. Catal., B, 2017)

(untitled) - Yuan, B.; Wang, Y.; Bian, H.; Shen, T.; Wu, Y.; Chen, Z. (Appl. Surf. Sci., 2013)

(untitled) - Lana-Villarreal, T.; Monllor-Satoca, D.; Gómez, R.; Salvador, P. (Electrochem. Commun., 2006)

(untitled) - Macak, J. M.; Tsuchiya, H.; Ghicov, A.; Yasuda, K.; Hahn, R.; Bauer, S.; Schmuki, P. (Curr. Opin. Solid State Mater. Sci., 2007)

Morphology and Growth of Titania Nanotubes. Nanostructuring and Applications - Albu, S. P. (Friedrich-Alexander Universität, 2012)

(untitled) - Kar, P.; Zhang, Y.; Farsinezhad, S.; Mohammadpour, A.; Wiltshire, B. D.; Sharma, H.; Shankar, K. (Chem. Commun., 2015)

(untitled) - Bervian, A.; Coser, E.; Pianaro, S. A.; Aguzzoli, C.; Pedott, A.; Khan, S.; Malfatti, C. d. F. (Mater. Res. (Sao Carlos, Braz.), 2018)

(untitled) - So, S.; Riboni, F.; Hwang, I.; Paul, D.; Hammond, J.; Tomanec, O.; Zboril, R.; Sadoway, D. R.; Schmuki, P. (Electrochim. Acta, 2017)

(untitled) - Chen, X.; Liu, L.; Yu, P. Y.; Mao, S. S. (Science, 2011)

(untitled) - Lai, C. W.; Sreekantan, S. (Electrochim. Acta, 2013)

(untitled) - Su, Y.; Zhang, X.; Zhou, M.; Han, S.; Lei, L. (J. Photochem. Photobiol., A, 2008)

(untitled) - Marien, C. B. D.; Cottineau, T.; Robert, D.; Drogui, P. (Appl. Catal., B, 2016)

(untitled) - Karthik, S.; Gopal, K. M.; Haripriya, E. P.; Sorachon, Y.; Maggie, P.; Oomman, K. V.; Craig, A. G. (Nanotechnology, 2007)

Inorganic Chemistry: Principles of Structure and Reactivity - Huheey, J. E.; Keiter, E. A.; Keiter, R. L.; Medhi, O. K. (Pearson Educatio, 2006)

(untitled) - Minella, M.; Faga, M. G.; Maurino, V.; Minero, C.; Pelizzetti, E.; Coluccia, S.; Martra, G. (Langmuir, 2010)

(untitled) - Monllor-Satoca, D.; Lana-Villarreal, T.; Gómez, R. (Langmuir, 2011)

(untitled) - Yu, J. C.; Yu, J.; Ho, W.; Jiang, Z.; Zhang, L. (Chem. Mater., 2002)

(untitled) - Giannakopoulou, T.; Todorova, N.; Vaimakis, T.; Ladas, S.; Trapalis, C. (J. Sol. Energy Eng., 2008)

(untitled) - Le, T. K.; Flahaut, D.; Martinez, H.; Pigot, T.; Nguyen, H. K. H.; Huynh, T. K. X. (Appl. Catal., B, 2014)

(untitled) - Cheng, X.; Liu, H.; Chen, Q.; Li, J.; Wang, P. (Electrochim. Acta, 2013)

(untitled) - Peighambardoust, N. S.; Khameneh Asl, S.; Mohammadpour, R.; Asl, S. K. (Electrochim. Acta, 2018)

(untitled) - Le, N. T.; Konstantinova, E. A.; Kokorin, A. I.; Kodom, T.; Alonso-Vante, N. (Chem. Phys. Lett., 2015)

(untitled) - Cheng, X.; Yu, X.; Xing, Z.; Yang, L. (Arabian J. Chem., 2016)

(untitled) - Sanchez-Martinez, A.; Ceballos-Sanchez, O.; Koop-Santa, C.; López-Mena, E. R.; Orozco-Guareño, E.; García-Guaderrama, M. (Ceram. Int., 2018)

(untitled) - Mazierski, P.; Łuczak, J.; Lisowski, W.; Winiarski, M. J.; Klimczuk, T.; Zaleska-Medynska, A. (Appl. Catal., B, 2017)

(untitled) - Yu, J.; Dai, G.; Cheng, B. (J. Phys. Chem. C, 2010)

(untitled) - Preethi, L. K.; Mathews, T.; Nand, M.; Jha, S. N.; Gopinath, C. S.; Dash, S. (Appl. Catal., B, 2017)

(untitled) - Sacco, A.; Garino, N.; Lamberti, A.; Pirri, C. F.; Quaglio, M. (Appl. Surf. Sci., 2017)

(untitled) - Acevedo-Peña, P.; González, F.; González, G.; González, I. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Acevedo-Peña, P.; Carrera-Crespo, J. E.; González, F.; González, I. (Electrochim. Acta, 2014)

(untitled) - Lee, S.; Park, I. J.; Kim, D. H.; Seong, W. M.; Kim, D. W.; Han, G. S.; Kim, J. Y.; Jung, H. S.; Hong, K. S. (Energy Environ. Sci., 2012)

(untitled) - Dozzi, M. V.; D’Andrea, C.; Ohtani, B.; Valentini, G.; Selli, E. (J. Phys. Chem. C, 2013)

(untitled) - Dozzi, M.; Selli, E. (Catalysts, 2013)

(untitled) - Santara, B.; Giri, P. K.; Imakita, K.; Fujii, M. (J. Phys. D: Appl. Phys., 2014)

(untitled) - Balachandran, U.; Eror, N. G. (J. Solid State Chem., 1982)

(untitled) - Hardcastle, F. D.; Ishihara, H.; Sharma, R.; Biris, A. S. (J. Mater. Chem., 2011)

(untitled) - Iliev, M. N.; Hadjiev, V. G.; Litvinchuk, A. P. (Vib. Spectrosc., 2013)

(untitled) - Hardcastle, F. D.; Ishihara, H.; Sharma, R.; Biris, A. S. (J. Mater. Chem., 2011)

(untitled) - Sun, Y.; Yan, K.; Wang, G.; Guo, W.; Ma, T. (J. Phys. Chem. C, 2011)

(untitled) - Yu, J.; Wang, B. (Appl. Catal., B, 2010)

(untitled) - Schmidt, A. M.; Azambuja, D. S.; Martini, E. M. A. (Corros. Sci., 2006)

Advances in Electrochemical Sciences and Engineering - Strehblow, H.-H. (Passivity of Metals, 2003)

(untitled) - Roy, P.; Berger, S.; Schmuki, P. (Angew. Chem., Int. Ed., 2011)

(untitled) - Kim, D.; Macak, J. M.; Schimidt-Stein, F.; Schmuki, P. (Nanotechnology, 2008)

(untitled) - Lee, K.; Ku, H.; Pak, D. (Chemosphere, 2016)

(untitled) - Zhao, Y.; Hoivik, N.; Wang, K. (Nano Energy, 2016)

(untitled) - Berger, T.; Lana-Villarreal, T.; Monllor-Satoca, D.; Gómez, R. (J. Phys. Chem. C, 2007)

(untitled) - Berger, T.; Monllor-Satoca, D.; Jankulovska, M.; Lana-Villarreal, T.; Gómez, R. (ChemPhysChem, 2012)

(untitled) - Arash, M.; Piyush, K.; Benjamin, D. W.; Abdelrahman, M. A.; Karthik, S. (Curr. Nanosci., 2015)

(untitled) - Wehrenfennig, C.; Palumbiny, C. M.; Snaith, H. J.; Johnston, M. B.; Schmidt-Mende, L.; Herz, L. M. (J. Phys. Chem. C, 2015)

(untitled) - Kapusta-Kołodziej, J.; Syrek, K.; Pawlik, A.; Jarosz, M.; Tynkevych, O.; Sulka, G. D. (Appl. Surf. Sci., 2017)

(untitled) - Leitner, K.; Schultze, J. W.; Stimming, U. (J. Electrochem. Soc., 1986)

(untitled) - Stimming, U. (Electrochim. Acta, 1986)

TiO2 Nanotube Arrays: Synthesis, Properties, and Applications - Grimes, C. A.; Mor, G. K. (Material Properties of TiO2 Nanotube Arrays: Structural, Elemental, Mechanical, Optical and Electrical, 2009)

TiO2 Nanotube Arrays: Synthesis, Properties, and Applications - Grimes, C. A.; Mor, G. K. (Springer US, 2009)

(untitled) - Dean, M. H.; Stimming, U. (Corros. Sci., 1989)

(untitled) - Radecka, M.; Rekas, M.; Trenczek-Zajac, A.; Zakrzewska, K. (J. Power Sources, 2008)

(untitled) - Sánchez-Tovar, R.; Fernández-Domene, R. M.; García-García, D. M.; García-Antón, J. (J. Power Sources, 2015)

(untitled) - Fernández-Domene, R. M.; Blasco-Tamarit, E.; García-García, D. M.; García Antón, J. (J. Electrochem. Soc., 2014)

(untitled) - Lu, X.; Wang, G.; Zhai, T.; Yu, M.; Gan, J.; Tong, Y.; Li, Y. (Nano Lett., 2012)

(untitled) - Fabregat-Santiago, F.; Barea, E. M.; Bisquert, J.; Mor, G. K.; Shankar, K.; Grimes, C. A. (J. Am. Chem. Soc., 2008)

(untitled) - Muñoz, A. G. (Electrochim. Acta, 2007)

(untitled) - Cohen, J. D.; Lang, D. V. (Phys. Rev. B, 1982)

(untitled) - Di Quarto, F.; La Mantia, F.; Santamaria, M. (Electrochim. Acta, 2005)

(untitled) - Gelderman, K.; Lee, L.; Donne, S. W. (J. Chem. Educ., 2007)

(untitled) - Bisschops, I.; Spanjers, H. (Environ. Technol., 2003)

(untitled) - Palma-Goyes, R. E.; Silva-Agredo, J.; González, I.; Torres-Palma, R. A. (Electrochim. Acta, 2014)

(untitled) - Oturan, M. A.; Aaron, J.-J. (Crit. Rev. Environ. Sci. Technol., 2014)

(untitled) - Arslan-Alaton, I.; Olmez-Hanci, T.; Shayin, S. (Environ. Technol., 2012)

(untitled) - Guerrero-Araque, D.; Ramírez-Ortega, D.; Acevedo-Peña, P.; Tzompantzi, F.; Calderón, H. A.; Gómez, R. (J. Photochem. Photobiol., A, 2017)

(untitled) - Hoffmann, M. R.; Martin, S. T.; Choi, W.; Bahnemann, D. W. (Chem. Rev., 1995)

(untitled) - Díaz-Real, J. A.; Ortiz-Ortega, E.; Gurrola, M. P.; Ledesma-Garcia, J.; Arriaga, L. G. (Electrochim. Acta, 2016)

(untitled) - Díaz-Real, J. A.; Ma, J.; Alonso-Vante, N. (Appl. Catal., B, 2016)

(untitled) - Nischk, M.; Mazierski, P.; Wei, Z.; Siuzdak, K.; Kouame, N. A.; Kowalska, E.; Remita, H.; Zaleska-Medynska, A. (Appl. Surf. Sci., 2016)

(untitled) - Zhang, T.; Liu, Y.; Liang, J.; Wang, D. (Appl. Surf. Sci., 2017)

(untitled) - Li, C.; Huang, Y.; Lai, K.; Rasco, B. A.; Fan, Y. (Food Control, 2016)

(untitled) - Anastasopoulos, J. A.; Soto Beobide, A.; Manikas, A. C.; Voyiatzis, G. A. (J. Raman Spectrosc., 2017)

(untitled) - Díaz-Real, J. A.; Dubed-Bandomo, G. C.; Galindo-de-la-Rosa, J.; Ortiz-Ortega, E.; Ledesma-García, J.; Arriaga, L. G. (Appl. Catal., B, 2018)